Acute appendicitis masquerading as food poisoning - Krish Patel; Garv Bhasin; Max Lasday, MS; Asha Plamoottil, MD; Latha Ganti, MD (Radiology Case Reports)
Acute appendicitis is a common surgical emergency. The underlying pathology in appendicitis occurs when the vermiform appendix, a vestigial organ connected to the large intestine, becomes swollen and inflamed. Some typical symptoms include abdominal pain, vomiting, fever, and appetite loss. Physical exam, imaging, and laboratory analyses are used to confirm the diagnosis. In this case report, a 15-year-old boy presented with vomiting and epigastric pain. Computed Tomography (CT) scans showed a fluid-filled appendix. Lab testing revealed elevated white blood cell counts, highlighting the importance of carefully analyzing test results. An appendectomy was performed which is the gold standard treatment for acute appendicitis. The patient’s clinical course demonstrates how clinical data can effectively narrow down a diagnosis of pediatric acute appendicitis.